Abstracts 2018
DOI: 10.1136/bmjopen-2018-ems.42
|View full text |Cite
|
Sign up to set email alerts
|

42 Effects of a general practitioner at scenes of serious injury: a systematic review

Abstract: Aim In Norway, each municipality is responsible for first line emergency healthcare, and has to have a general practitioner (GP) on call continuously. GPs are expected to assist patients and ambulance personnel at the site of severe injuries or illnesses. The Norwegian society invests substantial resources into emergency care, and it is desirable to find evidence to inform this practice. This systematic review aimed to examine how survival, time spent at the scene, the choice of transport destination, assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As ambulance services and PCDs are the backbone of the prehospital trauma care in Norway [ 7 ], EMCCs should always alert both the PCD and ambulance in the event of a severe incident, as required by the guidelines in emergency medicine regulations [ 4 ]. There is uncertainty about the possible effects of having a PCD at the scene of accident [ 15 ], and we could argue that the National Trauma Plan is not up to date, by involving the PCD. However, emergency trauma situations are initially often unclear, there could be several injured, more or less severe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ambulance services and PCDs are the backbone of the prehospital trauma care in Norway [ 7 ], EMCCs should always alert both the PCD and ambulance in the event of a severe incident, as required by the guidelines in emergency medicine regulations [ 4 ]. There is uncertainty about the possible effects of having a PCD at the scene of accident [ 15 ], and we could argue that the National Trauma Plan is not up to date, by involving the PCD. However, emergency trauma situations are initially often unclear, there could be several injured, more or less severe.…”
Section: Discussionmentioning
confidence: 99%
“…Less over-triage would also ease the burden on hospitals. However, a systematic review found no studies on the effect of having a PCD at the scene of an accident [ 15 ]. The PCD needs to master emergency treatment both in a team setting together with ambulance staff [ 16 , 17 ] and alone as the first healthcare responder attending to a trauma patient.…”
Section: Introductionmentioning
confidence: 99%
“…This was likely due to long time that it would take for the GP to travel to the patient in many cases. Few studies have examined the effects of GP attendance in acute situations [25]; however, Norwegian legislation imposes GPs to call-out when needed [2], ambulance workers prefer GPs to be present in challenging prehospital emergencies [26] and GPs claim improved patient care when involved [27]. Anticipated reasons for low involvement of medical professionals other than ambulance workers during patient transport can include a stable condition of the patient, a less severe medical problem than initial indicated, or a concurrent conflict for the GP.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is one example of an acute situation that requires fast and correct diagnosis with minimal pre-hospital treatment. There is scarce evidence for which situations continuous observation by a physician is required and further research is needed [25,27]. Still, attendance by physicians is probably improving the quality of the patient assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review was originally commissioned by the Norwegian National Advisory Unit on Trauma, and preliminary results were presented in a report in June 2017 …”
Section: Introductionmentioning
confidence: 99%